Design measurement for food packaging design: a design development - Raja Abdul Rahman, Raja Intan Suhaylah; Bidin, Azman; Lim, Yan Peng (European Publisher Ltd., 2020)
Design quantification occurs not only in the field of industry, but also academic. In order to fulfil the end- users needs, the significance of design quantification must be empirically comprehended. Product test, experimental stimulus and sampling procedures are among the methods that have been applied in this study. This study also acknowledges the relevant opinion of individuals who possess design awareness in offering design measurement method to quantify design and visual representation. Centrality Visual Product Aesthetics (CVPA) is a measurement that encounters four (4) values for design analysis. The sampling procedures took place with selected population that consist of design students. These selected students are the visualising consumers for packaging design. Thus, it is reported they attend more towards to visual design elements that make them have better preferences in making product choices. The design framework of this study focuses on the ninth goal in promoting the industry, innovation, as well as infrastructure by utilising a quantitative methodology in order to accomplish the United Nation’s Sustainable Development Goals. The results show that people with design sensitivity have stronger experiences and perceived values towards an aesthetic product. This design measurement has the possibility of the integration of a design process, particularly for an aesthetically pleasing sustainable packaging design.